Gamification in Language Learning: Strategies and Impacts - Rachman, Azhariah; Nishida, Daiki; Liliani Husain, Desy Liliani (Journal International of Lingua and Technology, 2024)
The integration of gamification in language learning has gained significant attention due to its potential to enhance engagement, motivation, and learning outcomes. Despite its growing popularity, there is a need for a comprehensive analysis of effective strategies and their impacts on learners. This study addresses this gap by exploring how gamification can be strategically implemented in language education. This research aims to identify effective gamification strategies in language learning and evaluate their impacts on learner motivation, engagement, and proficiency. A mixed-methods approach was employed, combining a systematic literature review of 50 studies from Scopus-indexed journals (Q1 and Q2) with a quasi-experimental study involving 120 language learners. Data were collected through surveys, interviews, and pre-post proficiency tests. The findings reveal that gamification strategies such as point systems, leaderboards, and narrative-driven tasks significantly improve learner motivation and engagement. Additionally, learners exposed to gamified environments demonstrated a 20% higher proficiency gain compared to traditional methods. Gamification is a powerful tool in language learning, offering innovative ways to enhance educational outcomes. However, its success depends on the careful design and alignment of game elements with learning objectives.